Digitising Journals: Conference on Future Strategies for European Libraries - Klugkist, Alex C. (LIBER Quarterly: The Journal of the Association of European Research Libraries, 1999)
The growing use of electronic journals leads to an ever increasing and widespread wish to retrospectively digitise journals. The process, however, is both costly and complicated and furthermore - basic standards are missing. With a view to working out a better basis for decision-making and examining the possibilities for European co-operation we are pleased to announce that a conference will be organized about: Digitising Journals: Conference on future strategies for European libraries. The Conference is organised by LIBER and Denmark’s Electronic Research Library Programme in co-operation with the European project DIEPER, the North American JSTOR project and NORDINFO, the Nordic Council for Scientific Information.